2022
DOI: 10.1049/hve2.12253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antioxidant depletion kinetic model and ageing behaviour of cross‐linked polyethylene cable insulation

Abstract: A concise kinetic model catering for the antioxidant reaction of thermally aged crosslinked polyethylene (XLPE) cable insulation before its abrupt performance deterioration is proposed for life prediction and condition assessment. The alternating current breakdown strength, elongation at break, carbonyl index, and pyrolysis activation energy of XLPE insulation are found to consistently display an abrupt change at a certain point of ageing time. This is strongly correlated to the depletion of the antioxidant wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The enhanced antioxidative ability of XLPE‐g‐TMPTMA can be attributed to the reduction of the initiator content, which would reduce the loss of antioxidant's activity during the crosslinking reaction. The addition of graftable antioxidant GA can significantly enhance the antioxidative properties of XLPE [20, 21], indicating that GA did not lose its antioxidative activity due to the crosslinking reaction. Due to the reduction of DCP and the introduction of GA, compared with XLPE, the OIT of XLPE‐g‐(TMPTMA‐co‐GA) was increased from 5.9 to 44.6 min, which indicated that the thermal oxidation stability of XLPE was significantly enhanced by co‐grafting TMPTMA and GA.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced antioxidative ability of XLPE‐g‐TMPTMA can be attributed to the reduction of the initiator content, which would reduce the loss of antioxidant's activity during the crosslinking reaction. The addition of graftable antioxidant GA can significantly enhance the antioxidative properties of XLPE [20, 21], indicating that GA did not lose its antioxidative activity due to the crosslinking reaction. Due to the reduction of DCP and the introduction of GA, compared with XLPE, the OIT of XLPE‐g‐(TMPTMA‐co‐GA) was increased from 5.9 to 44.6 min, which indicated that the thermal oxidation stability of XLPE was significantly enhanced by co‐grafting TMPTMA and GA.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of aging time, the cross‐linked chemical bonds are gradually broken and reformed into alkyl groups. The macroscopic manifestation is the decrease of stress and strain of shielding material 28 . When the aging time is 60 days, the molecular chains of CB + EVA and CB + EEA shielding materials are seriously damaged, the interface bonding force between carbon black and matrix is weakened, and the stress dispersion ability of carbon black is weakened.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Additionally, the expansion and separation of the EPC phase leads to more structural defects between the phases, resulting in the materials being easier to rupture during the tensile process and the deterioration of elongation at break. The decline in crystallinity shown in Figure 3h is responsible for the deterioration of the electrical properties, 39,40 which is also suggested to be caused by the breakage of crystal structures resulting from the expanded EPC phase.…”
mentioning
confidence: 99%